Macroalgae Inventory at Kondang Merak Beach, Malang RegencyRegency - Agustina, Citra Sari; Kartikasari, Desi; Abidin, Zainal; Maulana, Muhammad Iqbal; Daffa, Allan Fa’iq (3BIO: Journal of Biological Science, Technology and Management, 2025)
Macroalgae is a type of tuberous plant that does not have a clear distinction between roots, stems, and leaves. Macroalgae also have a very important role ecologically in marine ecosystems and have been widely utilized in the cosmetics industry, food sources and their potential as medicines due to their bioactive compounds. The presence of macroalgae in the waters is found in the intertidal zone and subtidal zone and occupies a variety of substrates in the waters. One location that has good potential regarding the presence of macroalgae is Kondang Merak Beach because of its natural ecosystem with the presence of mangrove vegetation, seagrasses, coral reefs, and protected forests. So this study aims to determine the types of macroalgae found at Kondang Merak Beach, Malang Regency. The research was conducted on 3 November 2024 in the Kondang Merak Beach area of Malang Regency. The research method used was free roaming with a qualitative descriptive approach. The sampling process was carried out at low tide around 05.00 WIB until 10.00 WIB, then the identification process was carried out in the field and laboratory. The results obtained nine species of macroalgae, namely Halimeda macroloba, Ulva lactuca, Padina gymnospora, Acanthophora spisifera, Hypnea valentiae, Gigartina papillate, Kappaphycus striatus, Galaxaura rugosa, and Palmaria palmata. The presence of macroalgae is also influenced by the abiotic conditions of the waters, the results of abiotic measurements show a temperature of 25.0°C, pH 7.67, DO 7 ppm, turbidity 34 NTU, TDS 14.6 mg/L, salinity 43 ‰, wind speed 1 m/s, light intensity 63372 lux, still in optimal conditions in supporting macroalgae life. Turbidity value of 34 NTU which tends to be rather high can be caused by strong ocean currents and hydro-oseanografi phenomena.